PENERAPAN E-LKPD BERBASIS MODEL PEMBELAJARAN DALAM PEMBELAJARAN IPA DI SEKOLAH - Reisa Salsabila Fardiana, Neng Kiane; Latip, Abdul; Abdurrahman, Dudung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
E-LKPD is an electronic learning tool that contains material, assignments and steps in learning activities to solve problems in certain learning. E-LKPD is often combined with learning models to achieve the expected goals. The use of E-LKPD in learning will be better if it is combined with relevant learning models. The purpose of writing this article is to convey the results of analysis from a literature review regarding the implementation of E-LKPD based on learning models in science in schools. Literature review analysis was carried out on 20 articles published from 2021-2024, by carrying out 5 literature review steps, namely selecting the topic to be reviewed, searching for articles on Google Scholar, selecting articles according to the specified criteria and focus of the study, conducting analysis and synthesis of the articles reviewed, and organizing the writing. The results of the literature review and analysis show that: 1) In science learning a number of learning models have been combined with E-LKPD, and have their own characteristics, several learning models that have been combined with E-LKPD include: PBL-based E-LKPD, E-LKPD PjBL based LKPD, STEM based E-LKPD, guided inquiry based E-LKPD, discovery learning based E-LKPD, open ended problem model based E-LKPD, 5E learning cycle model based E-LKPD, contextual based E-LKPD, E- RADEC based LKPD, ARCS based E-LKPD, SSC type PBL based E-LKPD, guided discovery learning model based E-LKPD. 2) The impact of implementing E-LKPD has various impacts, namely increasing several student abilities such as critical thinking, creative thinking, scientific literacy and science process skills, apart from increasing learning motivation and student learning outcomes in science learning.